2010
DOI: 10.1039/b9nr00415g
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional CdS nanostructures: synthesis, properties, and applications

Abstract: One-dimensional (1D) semiconductor nanostructures are of prime interest due to their potential in investigating the size and dimensionality dependence of the materials' physical properties and constructing nanoscale electronic and optoelectronic devices. Cadmium sulfide (CdS) is an important semiconductor compound of the II-VI group, and its synthesis and properties have been of growing interest owing to prominent applications in several fields. This article provides a comprehensive review of the state-of-the-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
188
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(194 citation statements)
references
References 154 publications
6
188
0
Order By: Relevance
“…Many promising studies have been revived already 1 and have been reported its applications in photodetectors, light emitting diodes (LED), field-emitters, transistors, sensors and solar cells etc. Recently, nanostructures of CdS have attracted lots of attentions due to excellent properties such as photoresponse, high sensitivity, high detectivity 2 photocatalytic activity, 3 stability, fast speed etc., 4 But synthesis of nanoscale structures need high temp growths and device fabrication requires sophisticated lithography processes.…”
Section: Introductionmentioning
confidence: 99%
“…Many promising studies have been revived already 1 and have been reported its applications in photodetectors, light emitting diodes (LED), field-emitters, transistors, sensors and solar cells etc. Recently, nanostructures of CdS have attracted lots of attentions due to excellent properties such as photoresponse, high sensitivity, high detectivity 2 photocatalytic activity, 3 stability, fast speed etc., 4 But synthesis of nanoscale structures need high temp growths and device fabrication requires sophisticated lithography processes.…”
Section: Introductionmentioning
confidence: 99%
“…CdS is a promising binary II -VI semiconductor used in variety of optoelectronic applications, including solar cell windows, laser communication, photoconductors, field effect transistors, sensors, photocatalysts, biological indicators, light emitting diodes, etc. [9][10][11][12]. It is a wide band gap semiconductor lightly soluble in water and highly soluble in acid.…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7][8] Recently, supercritical uid (SCF) growth methods have enabled the large scale production of Si and Ge nanowires in a robust, relatively inexpensive manner. 9 Various templated growth methods have been employed for growing small diameter Ge nanowires (<15 nm), including the use of anodic alumina oxide and silica membranes. [10][11][12][13] The high-diffusivity of a supercritical uid enables rapid transport of precursors into the pores of many templates, permitting swi nucleation and growth of nanowires.…”
Section: Introductionmentioning
confidence: 99%